Evaluation of Nutritional Status using Head Circumference among Bhil, Dhodia and Kinnaura tribal Preschool Children, India - Kumar Kshatriya, Gautam; Kanti Roy, Pijush; Biswas, Saheli; Chanak, Mahua; Bose, Kaushik (Indian Journal of Child Health, 2024)
Background: Undernutrition is a major problem in developing countries, especially among tribal pre-school children. Many studies have been undertaken on preschool tribal children in different parts of India, but by considering different ecological zones, no previous studies have been taken into account for determining nutritional status using head circumference. Head circumference for age Z-score (HCAZ) is also a useful index for determining the nutritional status of pre-school children. Objectives: The aim of the study is to assess the nutritional status based on head circumference of preschool children of the Bhil, Dhodia and Kinnaura tribes. Methods: The present study was undertaken among 509 boys and 476 girls. Among which, 168 boys and 185 girls belonged to the Bhil tribe from Barmer district, 164 boys and 142 girls belonged to the Dhodia tribe from Valsad district, and 177 boys and 149 girls belonged to the Kinnaura tribe from Kinnaur district. WHO Child Growth Standards (2007) were utilized to determine Z-scores for head circumference for age (HCAZ). The standard formula was used to compute HCAZ: Z-score= (X- Median value of WHO 2007)/ standard deviation, WHO (2007). Moderately undernourished: